Changes in ganglion cells during retinal degeneration. (4th August 2016) - Saha, Susmita; Greferath, Ursula; Vessey, Kirstan A.; Grayden, David B.; Burkitt, Anthony N.; Fletcher, Erica L.
Graphical abstract: Highlights: Excitatory inputs are reduced on ON ganglion cells in retinal degeneration. Inhibitory inputs are reduced on OFF ganglion cells in retinal degeneration. There is a loss in ON bipolar cells in retinal degeneration. These data may explain functional changes in ganglion cells in retinal degeneration. Abstract: Inherited retinal degeneration such as retinitis pigmentosa (RP) is associated with photoreceptor loss and concomitant morphological and functional changes in the inner retina. It is not known whether these changes are associated with changes in the density and distribution of synaptic inputs to retinal ganglion cells (RGCs). We quantified changes in ganglion cell density in rd1 and age-matched C57BL/6J-(wildtype, WT) mice using the immunocytochemical marker, RBPMS. Our data revealed that following complete loss of photoreceptors, (∼3 months of age), there was a reduction in ganglion cell density in the peripheral retina. We next examined changes in synaptic inputs to A type ganglion cells by performing double labeling experiments in mice with the ganglion cell reporter lines, rd1-Thy1 and age-matched wildtype-Thy1. Ribbon synapses were identified by co-labelling with CtBP2 (RIBEYE) and conventional synapses with the clustering molecule, gephyrin. ON RGCs showed a significant reduction in RIBEYE-immunoreactive synapse density while OFF RGCs showed a significant reduction in the gephyrin-immmunoreactive synapse density. Distribution patterns of both synaptic markers across the dendritic trees of RGCs were unchanged. The change in synaptic inputs to RGCs was associated with a reduction in the number of immunolabeled rod bipolar and ON cone bipolar cells. These results suggest that functional changes reported in ganglion cells during retinal degeneration could be attributed to loss of synaptic inputs.